Pengembangan Sistem Informasi Pemantauan Keuangan Desa Berbasis Website pada Kantor Kecamatan Mejobo - Nurhaliza, Aulia; Triyanto, Wiwit Agus (Universitas Pahlawan Tuanku Tambusai, 2026)
Transparency and accountability in village finances are often hampered by technical application constraints and limited human resources in the field. To address these issues, this community service activity aims to develop and implement a web-based village financial monitoring information system that can be accessed in real time by sub-district governments and village officials. A participatory approach was taken through the diffusion of science and technology, training, and intensive mentoring; the system was built using PHP–MySQL and designed with a user-friendly interface for ease of operation by village officials. Implementation in several partner villages demonstrated improved recording and reporting efficiency, ease of cross-village monitoring by sub-districts, and increased public information transparency. User satisfaction surveys recorded positive responses, although improvements to certain technical features are still needed. These findings emphasize the importance of simple yet adaptive technology support to strengthen village financial governance and offer a model for replication of village financial management digitalization in other regions.